Dynamic Complexes in the Chaperonin-Mediated Protein Folding Cycle - Weiss, Celeste; Jebara, Fady; Nisemblat, Shahar; Azem, Abdussalam (Frontiers in Molecular Biosciences, 2016)
The GroEL-GroES chaperonin system is probably one of the most studied chaperone systems at the level of the molecular mechanism. Since the first reports of a bacterial gene involved in phage morphogenesis in 1972, these proteins have stimulated intensive research for over 40 years. During this time, detailed structural and functional studies have yielded constantly evolving concepts of the chaperonin mechanism of action. Despite of almost three decades of research on this oligomeric protein, certain aspects of its function remain controversial. In this review, we highlight one central aspect of its function, namely, the active intermediates of its reaction cycle, and present how research to this day continues to change our understanding of chaperonin-mediated protein folding.